Refining Low Strain Pile Integrity Testing for Minor Flaw Detection with Complex Wavelet Transform - Loseva, Elizaveta; Lozovsky, Ilya; Zhostkov, Ruslan (Salehan Institute of Higher Education, 2024)
The structural integrity of pile foundations is critical for the safety and longevity of buildings and infrastructure. Low strain impact testing is a widely used non-destructive method for assessing pile length and identifying significant defects; however, its sensitivity to minor flaws remains limited. This study aims to enhance the detection capabilities of low strain testing for minor defects by proposing an improved methodology. We conducted field tests on ten piles with small, artificially introduced flaws and complemented these tests with three-dimensional numerical simulations. Initial time-domain analyses of both field and simulated data, using low-frequency wave excitation, did not reveal distinct signal features indicative of defects. To address this limitation, we employed a set of hammers with varying weights and head materials for wave excitation, simulated with different input force pulse durations. We further applied Complex Continuous Wavelet Transform (CCWT) for time-frequency analysis of the acquired signals, which effectively identified minor defects through characteristic changes in wavelet coefficient phase angles at expected timestamps. The consistency of CCWT phase spectrum features across signals from different hammers, considering the varying sensitivities of wave excitations, facilitates the differentiation of genuine flaw-induced phase shifts from noise. The study's findings were integrated into an improved low strain pile integrity testing workflow, enhancing the method's accuracy in detecting minor flaws. Doi: 10.28991/CEJ-2024-010-10-05 Full Text: PDF